Corporate tax harmonization in the EU. - Bettendorf, L; Devereux, M; van der Horst, A; Loretz, S; de Mooij, R (Blackwell Publishing, 2010)
This paper explores the economic consequences of proposed EU reforms for a common consolidated corporate tax base. The reforms replace separate accounting with formula apportionment as a way to allocate corporate tax bases across countries. To assess the economic implications, we use a numerical computable general equilibrium (CGE) model for Europe. It encompasses several decision margins of firms such as marginal investment, FDI decisions, and multinational profit shifting. The simulations suggest that consolidation does not yield substantial welfare gains for Europe. The variation of effects across countries is large and depends on the choice of the apportionment formula. Consolidation with formula apportionment does not weaken incentives for tax competition. Tax competition instead offers a rationale for rate harmonization, in addition to base harmonization.